(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: The study was conducted on 787 small business owners in Nghe An province to determine the prevalence and related factors for tinea pedis. Methods: A descriptive research method, direct examination in 20% KOH media and fungal culture in Saboraud medium with pH < 5.5 and antibiotics were employed. Fungal species were determined based on species identification key. Results: The prevalence of tinea pedis was 15.8%, increasing by age, specifically 5.73% in the age group ≤ 39 years old, 10.65% in the age group of 40 - 49 years old, and 36.11% in the age group ≥ 50 years old. Multivariate correlation analysis showed some factors associated with tinea pedis, including age group ≥ 50 with [OR = 2.65, 95%CI: 1.70 – 4.13, p < 0.01] and people with seafood trading with [OR = 1.79, 95%CI: 1.04 – 3.08 p < 0.05]. Conclusions: The prevalence of tinea pedis in the small business owners in Nghe An was 15.5%. There was a relationship between age, seafood trading and tinea pedis.